2011
DOI: 10.1071/ch10471
|View full text |Cite
|
Sign up to set email alerts
|

A Potential New RAFT - Click Reaction or a Cautionary Note on the Use of Diazomethane to Methylate RAFT-synthesized Polymers

Abstract: It has been found that diazomethane undergoes a facile 1,3-dipolar cycloaddition with both dithiobenzoate RAFT agents and the dithiobenzoate end-groups of polymers formed by RAFT polymerization. Thus, 2-cyanoprop-2-yl dithiobenzoate on treatment with diazomethane at room temperature provided a mixture of stereoisomeric 1,3-dithiolanes in near quantitative (495%) yield. A low-molecular-weight RAFT-synthesized poly(methyl methacrylate) with dithiobenzoate end-groups underwent similar reaction as indicated by imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
1
14
0
2
Order By: Relevance
“…Consistent with their high activity as RAFT agents, the dithiobenzoates are also more reactive in other contexts. In particular, the dithiobenzoate end groups are more readily removed or transformed, which can be essential or advantageous in many biomedical and optoelectronic applications . However, the use of dithiobenzoates in controlling polymerization of styrenes and acrylates has significantly diminished in recent years, mainly in favor of trithiocarbonate RAFT agents, which generally are more readily synthesized, are less sensitive to hydrolytic and most other forms of degradation, and polymerizations with these reagents generally display much less and (sometimes) no discernable retardation.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with their high activity as RAFT agents, the dithiobenzoates are also more reactive in other contexts. In particular, the dithiobenzoate end groups are more readily removed or transformed, which can be essential or advantageous in many biomedical and optoelectronic applications . However, the use of dithiobenzoates in controlling polymerization of styrenes and acrylates has significantly diminished in recent years, mainly in favor of trithiocarbonate RAFT agents, which generally are more readily synthesized, are less sensitive to hydrolytic and most other forms of degradation, and polymerizations with these reagents generally display much less and (sometimes) no discernable retardation.…”
Section: Introductionmentioning
confidence: 99%
“…[309] The Thiocarbonyl 1,3-Dipolar Cycloaddition Reaction It has been found that diazomethane undergoes a facile 1,3-dipolar cycloaddition with dithiobenzoate RAFT agents and with dithiobenzoate end-groups of polymers formed by reversible addition-fragmentation chain transfer (RAFT) polymerization. [181] Thus, 2-cyanoprop-2-yl dithiobenzoate (12), on treatment with diazomethane at room temperature, provided stereoisomeric 1,3-dithiolanes in near quantitative (.95 %) yield. A low molar mass RAFT-synthesized poly(MMA) with dithiobenzoate end-groups underwent similar reaction as indicated by immediate decolourization and a quantitative doubling of molar mass.…”
Section: Click Reactionsmentioning
confidence: 99%
“…S S * BzMA [161] MMA [162] PEGMA [163] 302 [164] 301 [165] 312 [166] 396 [167] MA [168] PFPVB [169] PVS [169] St [132,162] 359 [170] St [171] BA [122] MMA/BDSMA [172] (MAA/TPMMA) [173] (MAA/293) [173] DEGMA/PEGMA [174] tBMA/DMAEMA/290 [175] MMA/LMA [163] 396-b-PEGMA [167] St/AcS [176] 4VP/EGDMA [177] (St-b-DMAEMA) [171] BzMA-b-HPMAm [161] DEGMA/PEGMA-b-DMAPMAm [174] PEGMA-b-MMA [163] LMA/MMA-b-PEGMA [163] 12 S S CN D* [178] MMA [178][179][180][181][182][183][184] PEGMA [111,185] GMA [186] 289 [186,187] 297 [188] 324 [189] 453 [190] iPOx [191] St [132,…”
mentioning
confidence: 99%
“…Silicones have been used as co-monomers incorporating other monomers and polymers to yield new properties. Condensation polymerization has been widely utilized to prepare the copolymers of silicone with urethane and amides [1,2]. The excellent properties of silicones with their marvelous thermal properties and stability, and relatively low glass transition temperatures have made this polymer ideal for manufacturing membranes [3][4][5].…”
Section: Introductionmentioning
confidence: 99%